P391 Young people's experiences with clinical care and preferences for delivery of new point-of-care tests for STIs in england. (14th July 2019) - Mcculloch, Hannah; Pacho, Agata; Geary, Rebecca; Fuller, Sebastian
Abstract : Background: Young people in the UK face multiple barriers to attending sexual health clinics (SHCs) and are at high risk for sexually transmitted infections (STIs), despite widely available free and confidential STI testing. Studies have shown that point-of-care tests (POCTs) for STIs, which can accurately diagnose and treat patients in one clinical visit, have potential to change clinical practice. It has been recommended that young people be consulted in advance of changes to care. Methods: We conducted a secondary analysis of qualitative in-depth interviews with young participants of the Precise study, which explored patient experiences of SHC services and their opinions of POCT implementation plans. Attendees were purposively sampled at three SHCs in England. Interviews were thematically analysed using NVivo (V10) to investigate young people's perceptions of their healthcare needs and preferences for POCTs. Results: Ten young people aged 17–22 years, including: three women-who-have-sex-with-men, four heterosexual men and three men-who-have-sex-with-men were interviewed between June 2015 and February 2016. Participants generally regarded the tests as innovations to improve SHC experiences including the potential to reduce time-to-results and receive results from trusted sexual health experts. Participants raised concerns that POCT implementation may shorten consultation times and changes to pathways may unintentionally impact on privacy and/or cause confusion. Participants suggested increase in provision of information to patients, including potential waiting times and self-sampling instructions, along with recommendations to safeguard privacy around sample provision and clinical consultation times. Conclusion: Many of our young participants discussed waiting for results to be anxiety-producing, with provision of POCTs mitigating this concern, increasing satisfaction with SHC care and potentially paving the way for increased attendance among this group. However, participants suggest that other barriers, specifically around confusion and privacy, are likely to mitigate positive effects if not addressed by appropriate clinical implementation plans. Disclosure: No significant relationships.